Glucocorticoids and insulin resistance in children with acute lymphoblastic leukemia - Chow, Eric J. (2012)
BACKGROUND: Children treated for acute lymphoblastic leukemia (ALL) are more likely to become overweight. Prolonged exposure to high-dose glucocorticoids may cause insulin resistance and facilitate development of this phenotype. PROCEDURE: Body mass indices (BMI) and insulin resistance (HOMA-IR) were prospectively measured among on- (n=31) and off-therapy participants (n=29). On-therapy participants were assessed prior to and while on glucocorticoids (5 days of prednisone 40 mg/m(2) or dexamethasone 6 mg/m(2)) given as part of routine maintenance chemotherapy, with a subset (n=10) receiving an intravenous glucose tolerance test (IVGTT) while on glucocorticoids. RESULTS: Baseline HOMA-IR values among on- and off-therapy participants were similar, but among on-therapy participants, HOMA-IR increased significantly with glucocorticoid exposure (median 3.39 vs. 1.26; p<0.01) with 45.2% of participants having values >4.39 (upper 2.5(th) percentile among normal weight adolescents). Although baseline HOMA-IR was significantly correlated with current BMI (r=0.48, p<0.01), change in HOMA-IR following steroid exposure was not correlated with any demographic or treatment characteristic including current BMI. Among those with IVGTT data, HOMA estimates in general correlated with values derived from a minimal model analysis (r~0.7). CONCLUSIONS: High-dose glucocorticoids given as part of routine chemotherapy were associated with a significantly increased insulin resistant state. Given the amount and duration of glucocorticoids children with ALL experience, these physiologic changes could be an important contributor to the development of therapy-related obesity.